PUSHING CONSUMERS TO PLANT-BASED MILK ALTERNATIVES: WHAT DRIVES THEM? - Insani, Rabani Jannata; Amalia, Fatya Alty (UI Scholars Hub, 2025)
Manuscript type: Research Article Research Aims: Describing the extent to which belief factors, supporting reasons, and opposing reasons can shape attitudes, thereby creating an intention to purchase plant-based milk products. Design/methodology/approach: Using Behavioral Reasoning Theory. Data were collected through quantitative methods from 407 respondents using a questionnaire, targeting those who had consumed plant-based milk. Analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS 3.0. Research Findings: The findings indicate that health beliefs, reasons for nutritional content, and supporting the environment significantly influence attitudes positively, while environmental beliefs have a positive but non-significant impact on attitudes. However, environmental support plays a crucial role in ensuring that environmental beliefs positively and significantly impact attitudes. Attitudes also have a strong influence on purchase intentions. Theoretical Contribution/Originality: This research applies using the Behavioral Reasoning Theory research model which has been adjusted for the research objectives to expand understanding of the factors that can shape attitudes so as to create purchase intentions for plant-based milk products Practitioner/Policy Implication: consumer beliefs, reasons for choosing, and reasons for not choosing plant-based milk significantly influence the formation of consumer attitudes, which ultimately lead to purchase intentions. Consumer beliefs such as health beliefs and environmental beliefs may not be sufficient to shape attitudes and generate purchase intentions for plant-based milk; factors such as reasons for and against are needed to shape attitudes and thus create purchase intentions. Research limitation/Implications: respondents had consumed plant-based milk, and the focus of this study was only on plant-based milk consumption.